Characterization of potent RSV neutralizing antibodies isolated from human memory B cells and identification of diverse RSV/hMPV cross-neutralizing epitopes. Issue 8 (17th November 2019) - Xiao, Xiao; Tang, Aimin; Cox, Kara S.; Wen, Zhiyun; Callahan, Cheryl; Sullivan, Nicole L.; Nahas, Deborah D.; Cosmi, Scott; Galli, Jennifer D.; Minnier, Michael; Verma, Deeptak; Babaoglu, Kerim; et al.
ABSTRACT: Respiratory syncytial virus (RSV) is a leading cause of lower respiratory tract infection in young children and older adults. Currently, no licensed vaccine is available, and therapeutic options are limited. The primary target of neutralizing antibodies to RSV is the surface fusion (F) glycoprotein. Understanding the recognition of antibodies with high neutralization potencies to RSV F antigen will provide critical insights in developing efficacious RSV antibodies and vaccines. In this study, we isolated and characterized a panel of monoclonal antibodies (mAbs) with high binding affinity to RSV prefusion F trimer and neutralization potency to RSV viruses. The mAbs were mapped to previously defined antigenic sites, and some that mapped to the same antigenic sites showed remarkable diversity in specificity, binding, and neutralization potencies. We found that the isolated site III mAbs shared highly conserved germline V-gene usage, but had different cross-reactivities to human metapneumovirus (hMPV), possibly due to the distinct modes/angles of interaction with RSV and hMPV F proteins. Furthermore, we identified a subset of potent RSV/hMPV cross-neutralizing mAbs that target antigenic site IV and the recently defined antigenic site V, while the majority of the mAbs targeting these two sites only neutralize RSV. Additionally, the isolated mAbs targeting site Ø were mono-specific for RSV and showed a wide range of neutralizing potencies on different RSV subtypes. Our data exemplify the diversity of anti-RSV mAbs and provide new insights into the immune recognition of respiratory viruses in the Pneumoviridae family.